THE INFLUENCE OF STRESS SYMPTOMS AND COPING STRATEGIES ON THE SUBJECTIVE WELL-BEING OF LONG DISTANCE MARRIAGE FAMILIES - Irbah, Anisa; Herawati, Tin; Musthofa, Musthofa (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2025)
Long-distance marriage poses profound psychological challenges for women, particularly in sustaining emotional well-being amid prolonged physical separation from their spouses. This study investigates the extent to which stress symptoms and coping strategies influence the subjective well-being of wives in long-distance marital arrangements. Employing a quantitative approach with a cross-sectional design, the research involved 41 wives residing in Bandung, Indonesia, who live apart from their husbands and are parenting adolescent children aged 13 to 21 years. Respondents were recruited using a non-probability snowball sampling technique. Descriptive results indicate that participants generally experienced mild stress symptoms, demonstrated moderate levels of coping strategies, and reported high subjective well-being. Correlation analyses revealed a significant negative association between stress symptoms and subjective well-being, while problem-focused coping strategies exhibited a significant positive correlation. Further regression analysis confirmed that stress symptoms negatively predicted subjective well-being (β = -0.44, p < 0.01), whereas coping strategies positively contributed to it (β = 0.38, p < 0.05). These findings underscore the critical role of adaptive coping mechanisms in mitigating psychological distress and enhancing emotional resilience among women managing long-distance marriages. This study offers valuable empirical insights for family practitioners and mental health professionals in developing culturally responsive interventions to support women in trans-local family structures.